Superior mesenteric artery aneurysm: very rare cause of epigastric pain - Salas-Cuadros, Dafne (2023)
The first successful case of surgical treatment of a superior mesenteric artery aneurysm is described at the Honorio Delgado Regional Hospital III in Arequipa. The case report involved a patient who had experienced 18 months of epigastric pain and was diagnosed with computed tomography and computed tomography. The patient underwent laparotomy for aneurysm resection and a bypass of the superior mesenteric artery was performed using a polytetrafluoroethylene graft. The patient had a rapid and uncomplicated recovery and has since progressed well. This type of aneurysm is rare, with no epidemiological data in Peru. Surgical treatment requires careful planning due to the high risk of rupture and mortality. Technological support is essential in the surgical approach of these patients, which is often a challenge in non-specialized public hospitals.